Elemen Budaya Sebagai Daya Tarik Wisata Di Desa Wisata Pengotan, Kecamatan Bangli, Kabupaten Bangli, Provinsi Bali - Santika, I Nengah Edi; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
Pengotan Tourism Village has unique culture that being a typical of the village itself. But, Pengotan Tourism Village isn’t known widely yet. The development which is not optimum and many obstacles make it happen. Based on that problems, this research aims to identify the cultural potentials, of Pengotan Tourism Village as a culture based tourism village in Bangli Subdistrict, Bangli Regency. The method that used in this research especially on analyzing the data is qualitative descriptive analysis to determine the potentials and the obstacles of development. The datas are collected through observation, interviews, literature study, and documentation. The informants are determined using purposive sampling technique. The result of this research is Pengotan Tourism Village has many potentials that can make it as a tourist attraction in Bangli Regency. The potentials are cultural such as handicrafts, tradition, history of Pengotan, architecture, arts and musics, community livelihood, religion, and language.   Keywords : potential culture , Pengotan Tourism Village, Tourist Attraction